A comparative study on the relationship between self-directed learning and academic achievement among Malaysian and Turkish undergraduates / Badli Esham Ahmad... [et al.] - Ahmad, Badli Esham; Ozturk, Mustafa; Abdullah@Baharum, Mohd Amli; Abdul Majid, Faizah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Self-directed Learning (SDL) is highly valued in the industry and is considered to be a valuable criterion for prospective employers, hence, it is pertinent for university students to develop and demonstrate their ability to be self-directed from their study years. This in turn would prepare them for the upcoming employment as the future workplace is more focused on the Industrial Revolution 4.0 This exploratory study aimed at identifying the level of SDL readiness among Malaysia and Turkey participants as well as comparing any SDL similarities between the two sets of participants. The study also looked at the relationship between SDL and academic achievement of the participants. Adapted version of the SDLRS was used in identifying the level of SDL readiness of the participants. Data was collected from one hundred and six participants from Malaysian and Turkish public universities and was analyzed using SPSS version 24. The findings from the study indicated that a majority of the participants are in the average or below average category of SDL readiness. It was also found that Malaysian and Turkish participants have similar SDL readiness level. Only a small percentage of the participants are highly self-directed. The study also found that SDL has a no significant relationship with academic achievement of the participants. This would indicate the importance of developing high SDL. It can be concluded that a majority of the participants in the study are not highly self-directed and a few contributing factors, cultural factor being one of them, are suggested behind the low scores. Suggestions were also given on how to develop SDL among the participants in order to prepare them for better assimilation into the industry.